Moving and handling patients at a glance - MacGregor, Hamish (At a glance series (Oxford, England), 2016)
"Moving and Handling Patients at a Glance provides an accessible introduction to the key theoretical underpinnings of moving and handling, including the legal aspects, biomechanics, risk assessment and safe principles of handling"--Provided by publisher.